Electrical conductivity of soybean seeds after storage in several environments - Vieira, R. D. [UNESP]; Tekrony, D. M.; Egli, D. B.; Rucker, M. (My University, 2001)
Membrane integrity, as measured by electrical conductivity (EC), is suggested as an indicator of seed vigor in soybean [Glycine max (L.) Merrill] seeds. This study evaluated the effect of storage time and temperature on EC of six soybean seed lots (two lots each of high, medium and low vigor). All seed lots were adjusted to 120 g kg-1 seed moisture, sealed in aluminum foil packets and placed in storage at 10 and 20°C or stored unsealed in multi-wall paper bags in warehouse (WH) conditions at Lexington, KY, USA for 486 days. Four of the six seed lots were also stored unsealed at 10°C. All seed lots were sampled at 3-month intervals and evaluated for seed moisture (SMC), standard germination (SG) and vigor [accelerated aging (AA) and EC]. After 91 and 204 days in storage, samples initially stored at 20°C and WH were moved to 10°C and sampled at the same intervals. Seed moisture content for unsealed samples equilibrated at 107 g kg-1 (± 9 g kg-1) in both the WH and 10°C environments. No change in SG occurred for seeds stored sealed (120 g kg-1) at 10°C, except for the low vigor seed lots which declined significantly at the last sample date. The AA germination declined significantly for all seed lots stored sealed at 10°C, however the EC did not change during the same storage period. Seeds stored sealed at 20°C and unsealed in the WH showed rapid declines in AA and SG and significant increases in EC. When these seeds were moved to 10°C, however, the AA continued to decline while the EC remained at the same level (no significant change) for the remainder of the seed storage period. Thus whilst the AA declined in all environments, the EC only increased at higher temperatures (20°C, WH) but showed little change during storage at 10°C. Thus, precautions must be taken if using EC to measure soybean seed vigor following storage at 10°C.